The promise of endogenous potential in times of crisis: Analysis of the effects of the Corona pandemic on the socio-economic embeddedness in local economies - Anna Herzog; Marieke Vomberg (REGION, 2021)
The measures against the spread of the Covid-19 virus have massive effects on local economies. By means of an explorative qualitative case study in deprived neighbourhoods in the Middle Lower Rhine region of Germany, this paper explicitly aims at examining the Corona pandemic's impact on their endogenous potential. In this context, the focus is on organisations whose main contribution lies in the fulfilment of the function of integration and communication. The analysis is based on theoretical concepts of the local economy, but it also refers to crisis as well as transition research, especially the multilevel perspective framework. By means of desktop research, a focus group with multipliers involved in local economic contexts as well as thirteen guideline-based interviews with the heads of local organisations, the subsequent analysis reveals the partially counteracting effects of the Corona pandemic on the organisations' socio-economic embeddedness. On the one hand, they are threatened by economic bottlenecks, by pending social consequences of a longer period without or with minimized offerings as well as by fear of contagion and exhaustion. While the organisation's perceived level of urgency varies greatly, their level of uncertainty is generally high. On the other hand, organisations of the local economy benefit from a positive push in the areas of digitization and new life and working environments (home-based work), as well as from a strengthening of local solidarity and cohesion.
Keywords: 330